Determination of enzyme activity of lactate dehydrogenase in gastric juice - Kocan Furman, José (1965)
Because enzymes , organic catalysts , involved in the most important and fundamental chemical reactions in the living organism , and considering its presence in tissues and fluids , it is no wonder that the study of them has the necessary scientific zeal awakened to reach an essential understanding of normal and pathological physiology. Many enzymes have been studied , but one of them , the Lactic Dehydrogenase , has received special interest lately in many medical research centers , hoping to apply their knowledge to the diagnosis and treatment of many diseases. Since the original report of Hill and Levy (1954 ) and Hill (1955) ( 10) , which demonstrated that lactate dehydrogenase activity is increased in the serum of patients with neoplastic disease ; many authors in subsequent investigations corroborated this work , indicating that this enzyme could be used in the clinical diagnosis of patients with neoplastic diseases.